Analysis of Agricultural Growth Using LQ And Shiftshare Methods (Case Study : Manokwari Regency, Indonesia) - Prima Jiwa Osly; Irfan Ihsani; Fulki Araswati; Rhonny Einsten Ririhena; Ardini Putri (Jurnal Infrastruktur, 2020)
Economic growth is an indicator of a process of economic development conducted both at the national and regional level. to increase economic growth that implemented through the effectiveness and efficiency of economic development, implementation of economic development needs to directed to the sectors that can give large multiplier effect on different sectors and the economy. Indonesia's economic development is closely related to agricultural development since Indonesia itself is an agrarian country that has most of its people as farmers. This research aims to find potential in the province of West Papua with selections of excellent commodities suitable to be developed and analyze sub-sector agriculture to the district economy Manokwari period 2013-2017 contributes. The method of analysis used is "Location Quotient" and Shift Share Analysis technique. The results showed that most of Manokwari district in West Papua Province has a base sector that is agriculture sector, services sector and building sector.